Teaching internship from the metaphorical lens of Filipino prospective teachers - Danilo V. Rogayan Jr.; Denn Harry R. Reusia (International Journal of Evaluation and Research in Education (IJERE), 2021)
Understanding prospective teachers’ (PTs) conceptions and perspectives about teaching internship may serve as an anchor for understanding their new experiences. The study explores Filipino PTs’ concepts of teaching internship through a metaphorical lens. Seventy-five PTs from a state-owned university in the Philippines served as the subjects of this qualitative inquiry. Data came from written narratives and explanations provided by the participants to describe their ideas on what a teaching internship is all about. The metaphoric images were enumerated, counted, interpreted, and classified to show meaningful patterns and themes. Findings showed that conceptions converged into six categories teaching internship as: 1) An endless learning venture; 2) A rewarding obstacle to surpass; 3) A chance to be a surrogate parent; 4) An enhancement of pedagogical competence; 5) An immersion in the actual workplace; and 6) An ultimate path towards becoming a teacher. Metaphors used by the participants were a mix of positive and negative symbolisms. The study offered possible descriptions for these conceptions and their implications on teacher education institutions (TEIs). The supervision of the off-campus teaching internship program could be enhanced at the onset of Education 4.0.